1992
DOI: 10.1161/01.str.23.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of cerebral hemorrhage in 236 consecutive cases in Brussels.

Abstract: Background and Purpose: Seasonal variation in the incidence of cerebral hemorrhage has been previously demonstrated. In this study, we sought to identify the climatological data best correlated with this seasonal variation.Methods: In a retrospectively studied sequential series of 236 patients with nontraumatic cerebral hemorrhage observed in Brussels over a period of 8 years, we cumulatively grouped the dates of stroke occurrence into a single calendar year.Results: We found marked seasonal variation in incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
1
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 12 publications
5
43
1
1
Order By: Relevance
“…The number of patients varied widely, and not all series were large enough to have the statistical power for reliable conclusions. 1,5,[11][12][13][14]16,[31][32][33][34][35][36] The diagnosis of ICH was confirmed by imaging studies or autopsy in a few studies, 2,6,13,15,32,33,37,38 and it is often unclear whether ICH was spontaneous or primary. 3-5,8 -12,14 -16,31-34,39,40 In some studies, cases were identified on the basis of International Classification of Diseases (ICD) discharge codes, 8,9,10,39 whereas others included subarachnoid hemorrhage (SAH) 32 or excluded elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of patients varied widely, and not all series were large enough to have the statistical power for reliable conclusions. 1,5,[11][12][13][14]16,[31][32][33][34][35][36] The diagnosis of ICH was confirmed by imaging studies or autopsy in a few studies, 2,6,13,15,32,33,37,38 and it is often unclear whether ICH was spontaneous or primary. 3-5,8 -12,14 -16,31-34,39,40 In some studies, cases were identified on the basis of International Classification of Diseases (ICD) discharge codes, 8,9,10,39 whereas others included subarachnoid hemorrhage (SAH) 32 or excluded elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…3-5,8 -12,14 -16,31-34,39,40 In some studies, cases were identified on the basis of International Classification of Diseases (ICD) discharge codes, 8,9,10,39 whereas others included subarachnoid hemorrhage (SAH) 32 or excluded elderly patients. 13 Among studies on the seasonal distribution of ICH, some found increased occurrence of ICH [1][2][3][4][5][6][7][8][9][10]13 in winter, whereas others indicated peaks in other seasons 11,14,37 or no significant seasonal variation at all. 16,[31][32][33][34][35]38,39 However, the most consistent seasonal variation described was a seasonal pattern with a peak of incidence in winter and a minimum in summer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9] Nevertheless, as reported in a recent review, 10 authors often described discordant effects of both air temperature and atmospheric pressure.…”
mentioning
confidence: 99%